Effect of tree age on chemical compounds of ancient Anatolian black pine (Pinus nigra subsp pallasiana) needles in Northwest Turkey - Turfan, Nezahat; Alay, Mehtap; Sarıyıldız, Temel (Sisef-Soc Italiana Selvicoltura Ecol Forestale, 2018)
Plant primary and secondary metabolites are chemical compounds synthesized for essential functions, such as growth and development (primary metabolites), and specific functions, such as pollinator attraction or defense against herbivory (secondary metabolites). Their concentrations in plants are genetically determined, but are also affected by environmental factors. Among these factors, plant age has been reported to influence plant chemical compounds under similar environmental conditions. We aimed to investigate the chemical compounds of ancient Anatolian black pine (Pinus nigra subsp. pallasiana) needles from trees of different ages. Needles of over 500-, 200-, 100-, 50-, and 25-year-old black pine trees growing under similar environmental conditions were sampled and analyzed for photosynthetic pigments (chlorophyll a, chlorophyll b and carotenoids), proline, total soluble protein, glucose, sucrose, total soluble sugar, peroxidation level (MDA-malondialdehyde), hydrogen peroxide (H2O2) and antioxidants such as ascorbate peroxidase (APX), catalase (CAT) and superoxide dismutase (SOD) activities. Significant differences for chemical composition associated with age were found. In general, results showed that over 500-year-old Anatolian black pine had the highest proline, total soluble protein, H2O2, sucrose, total soluble carbohydrates, APX, CAT and SOD concentrations, whereas they had the lowest chlorophyll a, total chlorophyll, total carotenoid and glucose concentrations. However, 200-year-old trees had the highest glucose, but the lowest chlorophyll b, proline, H2O2 and total soluble carbohydrates. 50- and 25-year-old trees together showed the highest chlorophyll a and b, total chlorophyll, total carotenoid and MDA, but lowest total soluble protein and sucrose. In conclusion, these results provide valuable insight into the chemical composition of Anatolian black pine needles in relation to their age, and can be used for complementing studies on tree growth-defence relationships.
Keywords: Ancient Trees; Anatolian Black Pine; Chemical Composition; Turkey